Hydraulic characterization of an activated sludge reactor with recycling system by tracer experiment and analytical models. (15th September 2016) - Sánchez, F.; Viedma, A.; Kaiser, A.S.
Abstract: Fluid dynamic behaviour plays an important role in wastewater treatment. An efficient treatment requires the inexistence of certain hydraulic problems such as dead zones or short-circuiting flows. Residence time distribution (RTD) analysis is an excellent technique for detecting these inefficiencies. However, many wastewater treatment installations include water or sludge recycling systems, which prevent us from carrying out a conventional tracer pulse experiment to obtain the RTD curve of the installation. This paper develops an RTD analysis of an activated sludge reactor with recycling system. A tracer experiment in the reactor is carried out. Three analytical models, derived from the conventional pulse model, are proposed to obtain the RTD curve of the reactor. An analysis of the results is made, studying which model is the most suitable for each situation. This paper is useful to analyse the hydraulic efficiency of reactors with recycling systems. Graphical abstract: Highlights: RTD is an interesting tool for characterising the flow pattern in WWTPs. Analytical models for obtaining the RTD of reactors with tracer reappearance. Experimental validation of the models in an operational plant. An analysis about which model is the most suitable for each situation is performed.